'Coercive confinement': An idea whose time has come?. Issue 1 (16th July 2020) - O'Donnell, Ian; O'Sullivan, Eoin
This article argues in favour of 'coercive confinement' as a useful addition to the criminological lexicon. It suggests that to properly understand a country's level of punitiveness requires consideration of a range of institutions that fall outside the remit of the formal criminal justice system. It also requires a generous longitudinal focus. Using Ireland as a case study, such an approach reveals that since the foundation of the state, the prison has gradually become ascendant. This might be read to imply a punitive turn. But when a broader view is taken to include involuntary detention in psychiatric hospitals, confinement in Magdalen homes and mother and baby homes, and detention in industrial and reformatory schools, the trajectory is strongly downward. This might be read to imply a national programme of decarceration. (In recent years, asylum seekers have been held in congregate settings that are experienced as prison-like and they must be factored into the analysis.) While some of these institutions may have been used with peculiar enthusiasm in Ireland, none are Irish inventions. It would be profitable to extend the idea of 'coercive confinement' to other nations with a view to adding some necessary nuance to our understanding of the reach and grip of the carceral state.